IgG1 B cell receptor signaling is inhibited by CD22 and promotes the development of B cells whose survival is less dependent on Ig alpha/beta - Nitschke, Lars; et al. (Journal of Experimental Medicine, 2007)
We describe a mouse strain in which B cell development relies either on the expression of membrane-bound immunoglobulin ( Ig) gamma 1 or mu heavy chains. Progenitor cells expressing gamma 1 chains from the beginning generate a peripheral B cell compartment of normal size with all subsets, but a partial block is seen at the pro- to pre-B cell transition. Accordingly, gamma 1-driven B cell development is disfavored in competition with developing B cells expressing a wild-type ( WT) IgH locus. However, the mutant B cells display a long half-life and accumulate in the mature B cell compartment, and even though partial truncation of the Ig alpha cytoplasmic tail compromises their development, it does not affect their maintenance, as it does in WT cells. IgG1-expressing B cells showed an enhanced Ca2+ response upon B cell receptor cross-linking, which was not due to a lack of inhibition by CD22. The enhanced Ca2+ response was also observed in mature B cells that had been switched from IgM to IgG1 expression in vivo. Collectively, these results suggest that the gamma 1 chain can exert a unique signaling function that can partially replace that of the Ig alpha/beta. heterodimer in B cell maintenance and may contribute to memory B cell physiology.